2010
DOI: 10.1590/s0103-90162010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of juvenile turbot (Scophthalmus maximus) fed varying dietary L-carnitine levels at different stocking densities

Abstract: Commercial farming of turbot (Scophthalmus maximus) at high stocking densities may lead to growth depression and increasing production costs. Moreover, the high levels of accumulated waste in an intensive system may cause rapid deterioration of water quality, which may undermine the production. Lcarnitine is known as a growth-enhancer which shows promise as mitigator of crowding effects. The effects of stocking densities (4, 8, 11 and 14 kg m -2 ) on growth performance, feed utilization and body composition we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…; Gonçalves et al . ). Many studies have shown that supplementing L‐carnitine in diets exhibits a positive growth‐enhancing effect in fry or juvenile fishes.…”
Section: Future Research Strategies On Nutritional Physiology and Appmentioning
confidence: 97%
“…; Gonçalves et al . ). Many studies have shown that supplementing L‐carnitine in diets exhibits a positive growth‐enhancing effect in fry or juvenile fishes.…”
Section: Future Research Strategies On Nutritional Physiology and Appmentioning
confidence: 97%
“…However, it may promote the energy efficiency of fatty acids, due to the increased mitochondrial lipid oxidation. It should be noted that the obtained results may differ according to experimental conditions, studied species, fish development phase, stress conditions, among other factors (Gonçalves et al, 2010). Li et al (2020) found that the action of L-carnitine supplementation in fish diets is directly linked to the abundance of individual macronutrients, including fatty acids, glucose, and amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported the positive effects of L-carnitine on some fish species, including: improved growth, reduction of muscle fat, better response against stress due to confinement, and adaptation to high levels of ammonia and high temperature variations (Gonçalves et al, 2010;Yang et al, 2012). However, the literature also shows contradictory results, which may be related to differences among the studied species, such as experimental conditions, management, and leaching and levels of the supplemented L-carnitine, among others (Gonçalves et al, 2010). Despite these reports, there are still no known studies on the inclusion of L-carnitine in the diet of pacu (Piaractus mesopotamicus Holmberg, 1887), which is native to South America and has an opportunistic omnivorous food habit, being well adapted to different production systems (Vaz et al, 2000).…”
Section: Introductionmentioning
confidence: 99%